Investigation of a Rectangular Dielectric Resonator Antenna Working in Higher Order Modes Using Perturbation Theory - null Neetu; Sachin Kumar; Binod Kumar Kanaujia; Sandeep Kumar Palaniswamy; Gaurav Varshney (International Journal of Antennas and Propagation)
Dielectric resonator antennas (DRAs) operating in higher order modes provide wideband, enhanced gain, and circularly polarized performance. This paper presents a simple perturbation theory for predicting the resonant frequency of higher order modes in perturbed rectangular DRAs (RDRAs). The proposed theory has been validated for isolated RDRA, two-layer DRA, and RDRA with rectangular- and cylindrical-shaped perturbations. To determine the accuracy of the proposed theory, the frequency computed from it is compared to simulated and measured results of higher order mode perturbed antennas available in the literature. The proposed theory can be easily applied to the design of perturbed DRAs that operate at higher order modes. Also, the theory can be extended to compute other antenna parameters.